STUDI TENTANG TOLERANSI BERAGAMA BAGI MAHASISWA-MAHASISWI PERGURUAN TINGGI KOTA KUPANG DALAM TERANG NOSTRA AETATE - Tamelab, Petrus; Bele, Graciana Amanda (STIPAS Keuskupan Agung Kupang, 2023)
The Indonesian state hopes that every religious follower will have an attitude of tolerance in social life. This tolerance is alsoexpected to be realized in the campus environment for students. The focus of this research is to study the attitude of tolerance between religious communities in accordance with the teachings of the Catholic Church in the Second Vatican Council document